Pemanfaatan Media Audio Visual untuk Meningkatkan Aktifitas Belajar Siswa pada Materi Seni Tari di Kelas VIII-1 SMP Negeri 2 Peusangan - Rahmmatullah Muslimin; Muhammad Fahlevy; M. Ahsanul Hakim; Thoriq Agamsyah; Nurul Amelia; Dhiyaaul Mubaarakh Bin Sulaiman; Tri Supadmi (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
This research aims to examine the use of audio-visual media in improving students' learning activities in traditional dance material at SMP Negeri 2 Peusangan. The background of this study is the lack of student engagement and difficulties in understanding dance movements when using only textbooks and traditional lecture methods. This research employs a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and verification. The findings indicate that the application of audio-visual media significantly enhances student motivation, focus, and participation in the learning process. By viewing video demonstrations, students are able to grasp the details of dance movements, attire, and musical accompaniment more effectively, leading to improved performance results compared to the previous method. The implication of this study is that audio-visual media serves as a highly effective tool for dance educators to facilitate learning, create a more dynamic atmosphere, and improve students' practical skills in traditional dance. This media-based approach is recommended for other subjects requiring visual demonstrations to maximize the learning experience and achieve educational goals.